Penguatan Kapasitas Green Entrepreneurship Diaspora Indonesia di Jepang melalui Pendekatan Green Business Model Canvas Berbasis Komunitas - Suranto, Suranto; Susilaningsih; Ahmad, Mujahidin; Mustofa, Rochman Hadi; Nugroho, Sidiq Permono; Siregar, Yani Sukriah; Lestari, Andriyani Puji (J-ABDIPAMAS (Jurnal Pengabdian Kepada Masyarakat), 2026)
ABSTRACT The transformation toward a green economy requires strengthening sustainable entrepreneurial capacity, including within Indonesian diaspora communities abroad. This International Partnership Community Service Program (PkM-KI) aims to enhance green entrepreneurship literacy and the capability to design green businesses based on the Green Business Model Canvas (GBMC) among the Indonesian diaspora in Japan. The program was implemented through a blended approach consisting of online webinars, offline workshops, and digital mentoring. A total of 30 participants attended the offline workshop and served as respondents for the pre-test and post-test. The results indicate an increase in the average score from 2.30 to 4.46, reflecting a gain of 2.16 points. The program produced tangible outputs in the form of community-based green business idea designs and the establishment of the Greenpreneur Indonesia–Japan forum. The program contributed to improving participants’ cognitive capacity, self-confidence, and strengthening the socio-economic networking of the diaspora. The blended community empowerment model based on GBMC proved to be effective and adaptive to the geographical and time constraints faced by participants. This program is recommended for replication among other diaspora communities as part of the internationalization of community engagement initiatives based on the green economy.   Keywords: green entrepreneurship, Indonesian diaspora, green business model canvas, community empowerment, green economy.   ABSTRAK Transformasi menuju ekonomi hijau menuntut penguatan kapasitas kewirausahaan berkelanjutan, termasuk pada komunitas diaspora Indonesia di luar negeri. Program Pengabdian kepada Masyarakat Kemitraan Internasional (PkM-KI) ini bertujuan meningkatkan literasi green entrepreneurship dan kemampuan perancangan usaha hijau berbasis Green Business Model Canvas (GBMC) pada diaspora Indonesia di Jepang. Kegiatan dilaksanakan melalui pendekatan blended: webinar daring, workshop luring, dan pendampingan digital. Sebanyak 30 peserta mengikuti workshop luring dan menjadi responden pre-test dan post-test Hasil menunjukkan peningkatan rata-rata skor dari 2,30 menjadi 4,46, dengan kenaikan sebesar 2,16 poin. Luaran konkret rancangan ide bisnis hijau berbasis komunitas serta terbentuknya forum Greenpreneur Indonesia–Jepang. Program ini berdampak pada peningkatan kapasitas kognitif, kepercayaan diri, serta penguatan jejaring sosial ekonomi diaspora. Model blended community empowerment berbasis GBMC terbukti efektif dan adaptif terhadap keterbatasan geografis dan waktu peserta. Program ini direkomendasikan untuk direplikasi pada komunitas diaspora lainnya sebagai bagian dari internasionalisasi pengabdian masyarakat berbasis green economy. Kata kunci: green entrepreneurship, diaspora Indonesia, green business model canvas, pemberdayaan komunitas, ekonomi hijau